A New Insight on Atherosclerosis Mechanism and Lipid-Lowering Drugs - Penghui Li; Wei Jiang (Reviews in Cardiovascular Medicine)
Atherosclerosis (AS) is a chronic vascular disease primarily affecting large and medium-sized arteries, involving complex pathological mechanisms such as inflammatory responses, lipid metabolism disorders and vascular plaque formation. In recent years, several emerging research hotspots have appeared in the field of atherosclerosis, including gut microbiota, pyroptosis, ferroptosis, autophagy, cuproptosis, exosomes and non-coding RNA. Traditional lipid-lowering drugs play a crucial role in the treatment of AS but are not able to significantly reverse the pathological changes. This article aims to summarize the latest research progress in the pathogenesis of AS and the diagnosis and treatment of the disease by comprehensively analyzing relevant literature mainly from the past five years. Additionally, the mechanisms of action and research advances of statins, cholesterol absorption inhibitors, fibrates and novel lipid-lowering drugs are reviewed to provide new insights into the diagnosis and treatment of AS.